2019
DOI: 10.1002/hrdq.21368
|View full text |Cite
|
Sign up to set email alerts
|

Informal workplace learning: Development and validation of a measure

Abstract: Informal workplace learning (IWL) is an important part of workrelated continuing education, especially in the case of bluecollar workers. The current article presents a new measure of IWL, which we developed based on the already existing Dynamic Model of Informal Learning by Tannenbaum et al. (2010). We extended the model to eight components by theoretical considerations, introducing a second-order structure. Each component is represented on the IWL scale with three items, the subscales have sound internal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
160
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(170 citation statements)
references
References 99 publications
(144 reference statements)
2
160
0
8
Order By: Relevance
“…The authors themselves indicated that the components may be subdivided even more in detail. Therefore, Decius et al (2019) extended the dynamic model from four to eight components by separating each component into two sub-factors. In their octagon model, experience/action was divided into trying/ applying own ideas and model learning; feedback into direct feedback and vicarious feedback; reflection into anticipatory reflection and subsequent reflection; intent to learn into intrinsic intent to learn and extrinsic intent to learn.…”
Section: Operationalizing Informal Workplace Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors themselves indicated that the components may be subdivided even more in detail. Therefore, Decius et al (2019) extended the dynamic model from four to eight components by separating each component into two sub-factors. In their octagon model, experience/action was divided into trying/ applying own ideas and model learning; feedback into direct feedback and vicarious feedback; reflection into anticipatory reflection and subsequent reflection; intent to learn into intrinsic intent to learn and extrinsic intent to learn.…”
Section: Operationalizing Informal Workplace Learningmentioning
confidence: 99%
“…The octagon model is a multilevel model with a core factor IWL, four components at the first level, and eight components at the second level. Building on the conceptual basis of the octagon model, Decius et al (2019) provided a measure for the operationalization of IWL. We decided to use this measure because it was developed for the target group of blue-collar workers and has a theoretical foundation with the octagon model, unlike other measures being developed in rather exploratory processes (e.g., Choi and Jacobs 2011;Froehlich et al 2017;Grosemans et al 2020;Noe et al 2013;Wolfson et al 2018).…”
Section: Operationalizing Informal Workplace Learningmentioning
confidence: 99%
See 2 more Smart Citations
“… 2019 ; Decius et al. 2019 ). Merkmale des Trainingsteilnehmenden wie beispielsweise die Motivation zum Transfer, die Transfervolition, aber auch Umgebungsfaktoren wie die Unterstützung von Kollegen und Vorgesetzten, die Möglichkeit von Belohnung oder Sanktion bei der Umsetzung des Gelernten wurden hierbei als entscheidende Faktoren für den Transfer, die über die Transfermotivation und die Transfervolition wirken, empirisch bestätigt (vgl.…”
unclassified